Spirit(ed) away: Preventing foetal alcohol syndrome with motivational interviewing and cognitive behavioural therapy - A. Jansen van Vuuren; D. Learmonth (South African Family Practice)
Foetal alcohol syndrome (FAS) is a growing concern in South Africa. In the Western Cape, prevalence rates for FAS are the highest in the world. Not surprisingly, the Western Cape also has some of the highest levels of alcohol consumption per capita. Although FAS is primarily caused by alcohol consumption during pregnancy, the high rate of FAS in South Africa originates from a multitude of complex factors. These factors include heritage, poverty, high levels of unemployment and low-paid menial jobs, depression, low self-esteem, low self-efficacy, increased accessibility to alcohol, lack of recreation, poor education, familial pressure, denial, cultural misconceptions and the smaller physiques of some of the women in the Western Cape. Holistic and comprehensive macro- and micro-level approaches are necessary in order to change the alcohol consumption trend that has developed over the last 300 years. No single strategy will reduce or eliminate the burden of alcohol misuse in this society. However, as the presented discussion suggests, combining the spirit of motivational interviewing (MI) with cognitive behavioural therapy (CBT) practice, borrowed from health psychological interventions for lifestyle-related chronic health conditions, holds promise for reducing the prevalence of FAS within Western Cape communities. These individual-based approaches have yet to be employed in South Africa despite the wealth of evidence that demonstrates their potential in targeting high-risk groups and reducing per capita alcohol consumption.